The Influence of Elevated Steeping Temperatures on the Resulting Malt Homogeneity and Malt Quality - Müller, Christian; Methner, Frank-Jürgen; Kleinwächter, Maik; Selmar, Dirk (BrewingScience, 2013)
Achieving a homogenous malt quality within industrial scale malt batches of up to 300?tons is a major goal for the malt industry. Malt analyses represent only small samples and merely give a rough mean score over thousands of kernels. Cytolytically badly modified or even ungerminated kernels may occur consequently leading to lautering and filtration problems e.g. due to high remaining unhydrolysed ?-glucan fractions. Published findings claim that relatively low temperatures during steeping and germination (12?17??C) are required to produce high quality malts, however, these processes consequently take 5 to 7?days excluding the kilning. Most of these studies were carried out several decades ago and new barley varieties with improved malting properties are available now.